The effects of course length on freestyle swimming speed in elite female and male swimmers - a comparison of swimmers at national and international level - Wolfrum, M.; Knechtle, B.; Rüst, C.; Rosemann, T.; Lepers, R. (SpringerPlus, 2013)
Freestyle swimming performance over 50 m, 100 m, 200 m, 400 m, 800 m and 1,500 m was compared on short (25 m) and long (50 m) course for 92,196 national swimmers (i.e. annual high score list Switzerland) and 1,104 international swimmers (i.e. finalists FINA World Championships) from 2000 to 2012. National and international swimmers of both sexes were on average 2.0 ± 0.6% faster on short than on long course. Sex-related differences in swimming speed were greater on short than on long course for international and national swimmers from 50 m to 800 m. Freestyle swimming performance improved across years for international swimmers in both short- and long-course whereas only male national swimmers were able to improve on short and long course events except for short course events on 800 m and 1,500 m. Performance in national women competing in short and long course events showed only improvements on 50 m, 100 m and 1,500 m across years. The sex-related differences in freestyle swimming performance showed no change for international swimmers. For national swimmers, the sex-related differences in freestyle swimming performance increased over time in long course from 50 m to 800 m, but decreased for 1,500 m. In conclusion, elite female and male freestyle swimmers at national and international level were about 2% faster on 25 m compared to 50 m course. During the 2000-2012 period, international as well as national swimmers (i.e. for national level predominantly men) improved freestyle swimming performance in both long and short course. More vigorous and optimized training programs focused on muscular force production in combination with efficient swimming skills might close the performance gap between elite swimmers at national level and FINA finalists. Further research especially including effects of anthropometric, biomechanical, and physiological factors is required to fully understand the effects of course length on freestyle swimming performance, and to determine whether course length has similar effects on other swim styles.